(untitled) (International journal of artificial intelligence, 2025)
Renewable energy sources are increasingly vital in addressing global energy demands while mitigating environmental impacts. This article explores the chemical principles underlying various renewable energy technologies, including solar, wind, bioenergy, and hydrogen fuels. Understanding the chemical reactions and materials involved is essential for improving efficiency and sustainability in energy production.